Pengaruh Intellectual Capital, Tax Avoidance dan Leverage Terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening - Nihayatul Qurrotulaini; Saiful Anwar (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi, 2021)
Intellectual capital, tax avoidance and leverage toward the company value with profitability as the variable of Intervening. This research uses quantitative research method with the use of doubled linear regrecy analysis and route analysis as a method of data analysis. This research uses secondary data of data panel on manufacture food and beverages company during period of 2014-2019. The method of sample taking used is purposive sampling. The sample in this research is 10 companies. The result of research shows that partially, the independent variable does not affect on dependent variable with coeficient value bigger than significancy level. Meanwhile, for the variable of Intervening, the value of the Counted-T from Intellectual Capital and Tax Avoidance variables shows bigger number than the Table-T. Thus occured an indirect relation between intellectual capital dan tax avoidance variables towards company value.